The first international mobility program: Global Project-Based Learning on Design of an intelligent control robotic system / Nor Azlan Othman … [et al.] - Othman, Nor Azlan; Damanhuri, Nor Salwa; Boudville, Rozan; Chong, Belinda Chiew Meng (UiTM Global @ Office of International Affairs, 2024)
The first international mobility programme, “Global Project Based Learning (gPBL) on Design of an intelligent control robotic system" was held at Universiti Teknologi MARA (UiTM) Pulau Pinang Branch, Malaysia from 3 to14 September 2023. This programme is the result of a Memorandum of Understanding (MoU) that was signed by UiTM and Fukuoka Institute of Technology (FIT), Japan on the 27 March 2023.